‘You’re never really free’: Understanding the barriers to desistance for registered sexual offenders in the community - Mann, Natalie (Criminology & criminal justice, 2021)
This article explores the relationship between the current model of community sex offender management, which is underpinned by mechanism of control and enforcement, and desistance from sexual offending. Utilizing data from qualitative interviews with 20 men convicted of sexual offences, we found that while existing practices offer some reassurance to those managing the public protection arena, they do little to encourage the substantive processes of identity change which is necessary for long-term desistance. This raises important considerations for how current risk management practices may be improved to encourage desistance and community reintegration.